Frequency of Subclinical Atherosclerosis in Patients with Rheumatoid Arthritis (Medical Forum Monthly, 2021)
Objective: To determine the frequency of subclinical atherosclerosis in patients with rheumatoid arthritis.Study Design: Observational / analytical study.Place and Duration of Study: This study was conducted at the Department of Orthopedic Surgery and Traumatology, Liaquat University of Medical and Health Sciences, Jamshoro from January 2019 to December 2019.Materials and Methods: Fifty patients of RA were contemplated and were analyzed. A large portion of the patients were more than 40 years old and experienced cardiovascular issues. Patients were assessed utilizing the normalized clinical meeting. Routine biochemical assessments were performed, furthermore, for incendiary markers, for example, CRP and ESR were acted in the clinic's clinical research facility. The rheumatoid factor (RF) was resolved utilizing ELISA. Illness action was estimated utilizing the sickness movement score 28 joints (DAS 28). The DAS 28 with CRP utilized as the score for illness the executives while the assent was gotten from the patients prior to gathering blood tests and performing tomography scan checks while the information was analyzed in SPSS and separated to have frequencies and rates.Results: The demographics of the 50 RA patients were studied. The average age of the RA patients was 55.21±7.64 years. Sixty four percent were female and 20 percent had a BMI >30. Systolic blood pressure and waist circumference and were found to be highly significant. The mean ± SD of BMI (kg/m2), WC, systolic & diastolic blood pressure, serum cholesterol (mg/dl), High density lipoproteins (mg/dl) and triglycerides (mg/dl) was 24.77±0.7, 88.86 ± 5.41, 160.85±4.61, 92.45 ± 5.31, 521 ± 20.72, 28.87 ± 3.43 and 210.84 ± 8.63. The mean ± SD for ESR and CRP (mg/dl) was identified as 85.12±8.74 and 25.74±5.87 while the fasting glucose (mg/dl) was 155.75±9.68. The Framingham risk score among rheumatoid male and female population was 1.6±0.51 and 7.10±3.31. The mean ± SD for disease duration (yrs) was 9.61 ±3.42 while the history of smoking and hypertension was found in 15 (30%) and 25 (50%) population. The majority of the patients belonged to rural community 35 (70%) and have lower class socioeconomical background 30 (60%). The mean ± SD for serum uric acid (mg/dl), DAS 28 and homocysteine (μmol/L) was 10.72±2.74, 6.78 ± 1.85 and 22.53±3.65.Conclusion: We determined the important non invasive biological markers for CVD in rheumatoid arthritis individuals.